Pengaruh Pengasuhan Terhadap Karakter Disiplin Anak - Bambang Wijanarko; Rini Sugiarti (JURNAL PENDIDIKAN ROKANIA, 2022)
One of the character values that needs to be developed and introduced to children in order to make an individual have a personality that has the quality of adalah disciplinary character where in the character of discipline there are many values that are needed by a child in everyday life and one of the keys to an individual's success is discipline. Discipline is a behavior that obeys and obeys the rules of the applicable rules. This study aims to empirically examine the influence of parenting on the character of children's discipline. The sempling technique in this study was a purposive sampling technique with the study subjects as many as 66 students with . This research was conducted at SDN Pandeanlamper 05 Semarang city. The research data were collected using two scales, namely the discipline character scale and the parenting scale, data analysis using a simple regression linear analysis using the JASP 016.3 program. The results showed that parenting had a positive and significant effect on the character of child discipline with p =.001 where p < 0.05. Keywords: child discipline, parenting, child character.